The effect of merging occupational role on office attire preferences of female managers associated to requisite trait aimed at a professional image - Posadas, Cathryn D.
The observation of women's increasing population on non-traditional field, which are male oriented ones and the adaptation of men's business suits which are the powersuits for women who wanted to "dress for success," lead to the study on determining the office attire preferences of female managers which gives impact to professional image. Questionnaire survey was given out to (12) female managers, working at from (7) different companies in Metro Manila. Pertaining questions about office attire preferences, and significance of clothes, which give impact to professional equality at workplace, were analyzed. Results were analyzed using the ranking method and Kramer's rank sum ranges at .05 level of significance. Results and findings of the study indicated that female managers preferred to wear office attire similar to men's business suits particularly blazers with lapel in feminized version. female managers did not significantly prefer non-collared office attire. On the other hand, office attire with neckwears indicated that respondents could not determine if they really prefer this style. Although, scarves were ranked first and were considered the most preferred neckwear than neckties. The findings also showed that respondents agreed on the impact of women's adaptation of men's business attire to professional equality. In relation to this, respondents were asked, as a manger how important they think clothes are, image projection was ranked first among other choices. Another, requisite traits of being manager such as high-competitive, team oriented, career oriented, optimistic, efficient, formal manner and organized were associated to office attire made up of blazer with lapel.